Mechanical Behavior and Its Influencing Factors on Engineered Cementitious Composite Linings - Zude Ding; Jiang Fu; Xiaoqin Li; Xiafei Ji (Advances in Materials Science and Engineering)
A 1/5-scale model test was used to analyze and compare the mechanical responses of engineered cementitious composite (ECC) lining and traditional concrete lining under vertically concentrated loading. Test results indicate that the major failure mode of the lining cross section is controlled by tensile stress. ECC linings express better cracking control capability and deformation performance than the traditional concrete tunnel linings. On this basis, the effects of loading direction, material tensile properties, soil stiffness, and model size on the mechanical behavior of ECC and R/ECC linings were analyzed by numerical calculation. Parametric analysis shows that the failure modes of ECC and R/ECC linings along different load directions are caused by the loss of bearing capacity due to the formation of three plastic hinges. Lining damage under horizontal loading is more concentrated than those under vertical and oblique loading. Improving the tensile properties of ECC materials can help enhance the load capacity and deformability of linings. Soil stiffness obviously affects the postpeak deformation behavior of ECC linings, as shown by the sharp increase of the load-displacement curve with the increase of soil stiffness. The peak load and corresponding displacement of linings demonstrate nonlinear increase with the increase in model size.